Diagnostic and Prognostic Value of Serum Golgi Protein 73 in Patients With Hepatitis B Virus‐Associated Acute‐on‐Chronic Liver Failure - Zheng‐ju Xu; Tao Xu; Qiao‐xia Ye; Yong‐fei Li; Tian‐huang Yang; Xiao‐man Zhang; Hui Lin; Hui‐guo Liu; Zhi‐jie Huang; Jian‐kun Shen (Immunity, Inflammation and Disease)
ABSTRACT Background and Aims The prognosis and severity of hepatitis B virus‐associated acute‐on‐chronic liver failure (HBV‐ACLF) cannot be well‐identified by serum biomarkers. The present study aims to determine the role of serum Golgi protein 73 (GP73) in predicting the prognosis and severity of liver necrotizing inflammation induced by HBV‐ACLF. Methods A total of 427 chronic HBV‐infected patients were included for the present study. Among these patients, 179 patients had chronic hepatitis B (CHB), 96 patients had HBV‐related liver cirrhosis (LC), and 152 patients had HBV‐ACLF. The baseline and dynamic changes in serum GP73 levels were measured and compared in CHB, LC and HBV‐ACLF patients. Results The serum GP73 levels were significantly greater in HBV‐ACLF patients when compared to CHB and LC patients. Furthermore, serum GP73 demonstrated excellent performance in distinguishing HBV‐ACLF from CHB and LC, with an area under the curve of 0.969 and 0.824, respectively. In the logistic regression analysis, a high GP73 level was identified as an independent risk factor associated with death within 3 months, and the optimal cut‐off level was 274.59 ng/mL. The serum GP73 levels significantly decreased and remained stable at approximately 6 months for survivors. Conclusion Serum GP73 may serve as a valuable biomarker for the diagnosis and prognosis prediction of HBV‐ACLF patients.